2020
DOI: 10.3390/jpm10030117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SH2B3, MTHFD1L, GGCX, and ITGB3 Gene Polymorphisms on theVariability on Warfarin Dosage Requirements and Susceptibility to CVD in the Jordanian Population

Abstract: The purpose of this study was to investigate the effects of the SH2B3, MTHFD1L, GGCX, and ITGB3 gene variants on the efficacy of warfarin treatment and its effects on the risk of cardiovascular disorders in Jordanian patients. The selected genes and their polymorphisms are involved in many Genome-Wide Association Study (GWAS) associated with cardiovascular disease and the variability of warfarin therapy. The current study conducted a genetic association and pharmacogenetics study in (212) Jordanian cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Those studies, aligning with others, have also shown that genetic variants could affect the patients’ response to cardiovascular drugs such as warfarin [ 47 , 48 ]. Therefore, coinciding with the goals of the current study of providing further evidence for possibly treating cardiovascular diseases like hypertension in a pharmacogenomic manner [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those studies, aligning with others, have also shown that genetic variants could affect the patients’ response to cardiovascular drugs such as warfarin [ 47 , 48 ]. Therefore, coinciding with the goals of the current study of providing further evidence for possibly treating cardiovascular diseases like hypertension in a pharmacogenomic manner [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous gene families have been implicated in cardiovascular diseases, with multiple genetic variations spread across the Jordanian population. Research has also indicated that several SNPs may also influence the response to cardiovascular medications such as warfarin [35][36][37][38][39][40][41][42][43][44]. However, the relationship between polymorphism within the ACE gene and HTN is still debatable and has so far been inconclusive; the reason is ethnic variations and geographic features.…”
Section: Introductionmentioning
confidence: 99%
“…MEF2A and SLC22A3-LPAL2-LPA have been studied widely in their correlation with cardiovascular diseases in multiple ethnicities and have been both identified as risk factors for cardiovascular diseases [19,21,29,30]. Genetic screening for multiple polymorphisms in Jordanian cardiovascular disease patients has been studied for multiple genes that are reported with warfarin responsiveness [31][32][33][34], however there is no record of studies that corelate MEF2A and SLC22A3-LPAL2-LPA with warfarin responsiveness in Jordanian cardiovascular disease patients. Increasing candidate genes that undergo warfarin pharmacodynamics and pharmacokinetics and studying their impacts on warfarin efficacy may help to find a precise way to adjust the appropriate dose of warfarin and reduce the risk of adverse drug reactions, resulting in more safe anticoagulant therapy.…”
Section: Introductionmentioning
confidence: 99%